RESPON SOSIAL DAN KEMAMPUAN SOSIALISASI PASIEN ISOLASI SOSIAL MELALUI MANAJEMEN KASUS SPESIALIS KEPERAWATAN JIWA - Azizah, Fajriyati Nur; Hamid, Achir Yani S.; Wardani, Ice Yulia (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Social isolation is a condition of loneliness felt by the individual being unable to make contact with other people. Social isolation can result in further on the issue of fulfillment of basic needs, so it would appear hallucinations that endanger themselves and others. Objective: The purpose of writing scientific papers to describe social changes, and socialization capabilities in social isolation’s patients using nursing care management of psychiatric specialist. Methods: Nursing orders given to 22 clients using nurses action, Social Skills Training (SST), and Cognitive-Behavioral and Social Skills Training (CBSST). Result: Results obtained reduction in social symptoms of social isolation mark that includes withdraw behaviour, interaction difficulties, refuse to communicate with others, fail to interact with others nearby, disabillity to participate in social activities, ignoring the environtment, and mistrust with others. The result also shown the improvement of socialization patient ability. Conclusion: : There were  reduction in symptoms  of social isolation obviously showed on social aspects as well as an increase in the client's ability to socialize. Recommendations of this study was to use a combination of measures such as nurses and specialist nurses Social Skills Training and Cognitive-Behavioral and Social Skills Training on clients with social isolation.   Key Words : Social Skills Training, Cognitive-Behavioral and Social Skills Training